Alexithymia and Depersonalization in Child Sex Offenders: The Role of Emotion Regulation. Issue 3 (2nd July 2016) - Lichev, Vladimir; Wolfradt, Uwe
ABSTRACT: The aim of the present study is to examine the constructs of alexithymia and depersonalization in a sample of child sex offenders and a matched control group. Alexithymia and depersonalization are personality constructs that indicate deficits in the ability to regulate emotions. Forty child sex offenders and 59 matched control subjects completed the Toronto Alexithymia Scale (TAS-26), the Rumination-Reflection Questionnaire (RRQ), and the Scale of Depersonalization Experiences (SDPE). The child sex offenders reported significantly more depersonalization experiences than the control subjects. Moreover, the child sex offenders showed also higher levels of alexithymia than the control group. They were less capable of describing and regulating their feelings. Logistic regression showed that depersonalization is a better discriminatory factor for sexual offensive behavior than alexithymia. The results are discussed in relation to emotion regulation and sexual offending.